Role of immunoglobulin 3´ regulatory region polymorphism in somatic hypermutation and vaccination response - Laine, Pauliina (My University, 2026)
Human immunoglobulin heavy chain 3´ regulatory regions (3´RR1 and 3´RR2) are gene regulatory regions downstream of Igalpha1 and Igalpha2 constant genes, respectively. The 3´RRs include three core enhancers: HS3, HS4 and HS1,2. Enhancer HS1,2 in 3´RR1 is polymorphic with four prevalent alleles. Enhancers HS3 and HS4 are not polymorphic. The 3´RRs has an important role in class switch recombination. Its role in somatic hypermutation is debated. The first aim of this study was to determine if HS1,2 alleles affected somatic hypermutation and, if so, do alleles affect mutation differently. Different individuals respond to vaccination differently. One factor influencing this is genetics, including polymorphism in genes related to immune response. Thus, the second aim of this study was to determine if 3´RR1 polymorphism affected vaccination response. A specific reporter genes assay (GFP4 loss assay) was used to evaluate the frequency somatic hypermutation induced by HS1,2 enhancer elements. To estimate the effect of enhancer variants on vaccination response, the Finnish part of BERT study was used. PCR assay was set up to determine HS1,2 alleles for patients. Vaccination response was evaluated by correlating obtained results to the quantity of total IgG, IgG subclasses and IgG avidity. HS1,2 alleles were found to increase somatic hypermutation, but only weakly. There were also some small differences between alleles. For vaccination response, the results showed no differences in quantity of total IgG amounts or IgG subclasses. The results were not fully conclusive on differences in antibody avidity. In conclusion, HS1,2 alleles have detectable, yet unlikely physiologically relevant, effect on somatic hypermutation. Additionally, there might be some differences between allelic variants, but these were neglectable. Differences in vaccination responses were not statistically significant between alleles, and investigation of larger populations is needed to establish potential effect of allelic variants.
Keywords: 3´ regulatory region, somatic hypermutation, vaccination response, HS1,2 enhancer, polymorphism